Seismic performance evaluation of a fire-exposed historical structure using an updated finite element model. (December 2019) - Günaydin, Murat
Abstract: This paper presents a seismic performance evaluation of a historical masonry structure. The process involves geometrical checking and seismic performance controls and also requires consideration of relevant codes and guidelines. Geometric checking was carried out in accordance with previous and newly-introduced Turkish Earthquake Codes. In order to obtain reliable results for seismic evaluation, the numerical model of the building was updated by means of non-destructive experimental measurement methods. The experimental measurement process was carried out using the Operational Modal Analysis method. The maximum error between the numerical and experimental natural frequencies, calculated as 37.11%, was reduced to 2.39% through the use of updating procedure. Time history seismic analysis was conducted on the updated finite element model using the Kocaeli 1999 earthquake record. Evaluation of the seismic performance of the structure was carried out with reference to a new guideline published specifically for assessment of historical structures. At the end of the analyses, maximum displacements and principal stresses were obtained and presented in detail using contour diagrams. In terms of displacement control, the structure showed only limited damage during the applied earthquake record: 0.0001 < 0.003. In other words, in terms of the new guideline, the structure behaved in a linear way when exposed to the selected earthquake. Highlights: Non-destructive experimental procedure was carried out on a fire-exposed historical masonry building. Numerical model of the building was updated by means of non-destructive experimental measurement methods. The maximum difference between the experimental and numerical frequencies was reduced from 37.11% to 2.39%. Geometric checking of the building was carried out in accordance with previous and newly-introduced Turkish Earthquake Codes. Seismic performance evaluation was carried out with reference to a new guideline published specifically for assessment of historical buildings.